The Effects of Two Root Canal Irrigants and Different Instruments on Dentin Microhardness ( In Vitro Study) - Wiaam MO AL-Ashou (University of Mosul, College of Dentistry, 2011)
Aims: To measure the microhardness of root canal dentin using two types of irrigating solutions( 0.2% Chlorhexidine and 5.25% Sodium Hypochlorite) with and with out use of different types of root canal files (Stainless Steel-K files, Nickel-Titanium K-files or rotary Nickel-Titanium files). Materials & methods: The teeth divided in to four groups according to the type of irrigating solutions that used during root canal instrumentation with the use of normal saline as a control group, then each group sub divided in groups according to the instrument used in the root canal preparation, then after irrigation and preparation the roots sliced and root dentin microhardness measured using Vicker,s microhardness machine. Results: The result of this study showed that the type of instrument and Chlorhexidine have no effect on the microhardness of root canal dentin while Sodium Hypochlorite significantly decrease the microhardness of root canal dentin especially when use with Stainless Steel K-files and Nickel-Titanium K-files than when used with rotary Nickel-Titanium files. Conclusion: The microhardness of root canal dentin not affected by the type of root canal instruments.,The use of 5.25% Sodium Hypoch-lorite as a root canal irrigation significantly reduce the microhardness of root dentin within 3 mi-nutes., The use of Sodium Hypochlorite as a root canal irrigant with stainless steel K-files or Nickel-Titanium K-files reduce the microhardness of root canal dentin to greater extend than when use with rotary Nickel-Titanium files because the working time required with Stainless Steel K-files or Nickel-Titanium K-files was on the average three times longer than the working time with rotary Nickel-Titanium files. The use of sodium hypochlorite as a root canal irrigant with stainless steel K-files or Nickel-Titanium K-files reduce the microhardness of root canal dentin